Media and Elections in India: Relevance for Central Asia - Sahai, Paramjit S. (2009)
This paper focuses on the role of media in respect of elections in a democracy, and in inculcating political culture of the electorate. The observations are based on the Indian experience and its relevance to central Asia. Highlighting the role of democracy as it has evolved over the years, the paper moves on to discuss the norms in the form of media indicators developed by the UNESCO and the guidelines prepared by the Association of Central and Eastern European Election Officials (ACEEEO) on media and elections, as relevant to the Central Asian region. The author draws attention to the media scene in India with the case of parliamentary elections in 2004. The Election Commission of India (ECI) interacts with the media in the election arena and the media itself has set norms for the coverage of elections. Media’s important role in shaping political process on an ongoing basis is evaluated. Finally, the paper deals with the possible areas, in which India and Central Asia could interact to strengthen the focus of democracy. A knowledge-sharing partnership could be developed through exchange of mutual experiences as best suited to each other and thus promote cooperation in building the professional capacity of the media workers.